Crushing droplets of coal-water fuel under conditions of high-speed impact on a solid barrier; International Communications in Heat and Mass Transfer; Vol. 157 - Syrodoy S. V. Semen Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Nigay N. A. Nataljya Andreevna; Kostoreva Zh. A. Zhanna Andreevna; Zamaltdinov R. R. Roman Rinatovich; Gutareva N. Yu. Nadezhda Yurievna; Akimov V. S. Vladislav Sayabekovich (2024, 2024)
Title screen